Improving clinical care of patients in Nipah outbreaks: moving beyond 'compassionate use' - Hassan, MZ; Rojek, A; Olliaro, P; Horby, P (Elsevier, 2025)
The 2024 Nipah outbreak in Kerala, India—its fifth in six years—and the recurring annual outbreaks in Bangladesh underscore the persistent threat posed by the Nipah virus (NiV) in the region. With a high mortality rate, human-to-human transmission potential, and the widespread presence of Pteropus bats, the natural reservoir, NiV remains a significant epidemic threat. Despite being a WHO priority pathogen, there has been no systematic effort to improve patient care for NiVD, leading to consistently poor outcomes. Current care relies on supportive measures and the ‘compassionate use’ of unapproved drugs like ribavirin and remdesivir. Drugs used ‘off-label’ during outbreaks can become the ‘standard of care’ without robust evidence of their safety or efficacy, complicating the testing of new therapies and perpetuating uncertainty about their true effectiveness. To improve NiVD care, we propose four key strategies: 1) Enhance early case detection, 2) optimize supportive care to improve outcomes and create a standard for future trials, 3) adopt a syndromic approach centered on encephalitis, and 4) explore innovative trial designs tailored to low case numbers as an alternative to ‘compassionate use’. By integrating these strategies, healthcare systems in NiV-endemic regions will be better equipped to manage both current and future outbreaks.